Identifying release for high bar skills - Golding, M.; Irwin, G.; Bezodis, I.; Exell, T.; Kerwin, D. G. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The release from the high bar for both dismounts and release re-grasp skills is a compulsory part of any high bar routine. Despite the importance of the instant of release there is no definitive scientific method to identify this instant in high bar gymnastics. Various methods of release definitions were compared using automatic motion analysis (200Hz), visual images (200Hz) and bar force (1000Hz). A single elite gymnast performed 5 dismounts and 5 Tkachevs. Differences between bar force derivatives and motion analysis suggest the approach taken can influence the key release parameters. Differences between skills also highlights that a global release definition may not be appropriate and further research should consider skill specific definitions of release from the bar.